2015
DOI: 10.1007/s00425-015-2426-x
|View full text |Cite
|
Sign up to set email alerts
|

OsNF-YC2 and OsNF-YC4 proteins inhibit flowering under long-day conditions in rice

Abstract: Plant NUCLEAR FACTOR Y (NF-Y) transcription factors control numerous developmental processes by forming heterotrimeric complexes, but little is known about their roles in flowering in rice. In this study, it is shown that some subunits of OsNF-YB and OsNF-YC interact with each other, and among them, OsNF-YC2 and OsNF-YC4 proteins regulate the photoperiodic flowering response of rice. Protein interaction studies showed that the physical interactions occurred between the three OsNF-YC proteins (OsNF-YC2, OsNF-YC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 45 publications
(61 reference statements)
1
42
0
Order By: Relevance
“…Trimer formation with OsNF-YC2 and OsNF-YC4 could not be formally demonstrated because of auto-activation of yeast reporters. However, dimeric interactions between OsNF-YC2 and OsNF-YB8, OsNF-YB10 and OsNF-YB11 have been reported [65]. Most importantly, genetic evidences support a role for OsNF-YC2 in the control of flowering in rice [65].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Trimer formation with OsNF-YC2 and OsNF-YC4 could not be formally demonstrated because of auto-activation of yeast reporters. However, dimeric interactions between OsNF-YC2 and OsNF-YB8, OsNF-YB10 and OsNF-YB11 have been reported [65]. Most importantly, genetic evidences support a role for OsNF-YC2 in the control of flowering in rice [65].…”
Section: Discussionmentioning
confidence: 99%
“…However, dimeric interactions between OsNF-YC2 and OsNF-YB8, OsNF-YB10 and OsNF-YB11 have been reported [65]. Most importantly, genetic evidences support a role for OsNF-YC2 in the control of flowering in rice [65]. Transcriptional silencing of OsNF-YC2 by RNA-interference (RNAi) resulted in accelerated flowering under LD conditions, whereas its overexpression under the maize ubiquitin promoter strongly delayed flowering [65].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, there is well established evidence that different NF-Y HFD subunits are involved in the regulation of timing of flowering in Arabidopsis (Wenkel et al, 2006;Chen et al, 2007;Cai et al, 2007;Kumimoto et al, 2008Kumimoto et al, , 2010Hackenberg et al, 2012;Hou et al, 2014;Cao et al, 2014), rice (Oryza sativa; Dai et al, 2012;Wei et al, 2010;Yan et al, 2011;Feng et al, 2014;Chen et al, 2014;Kim et al, 2016;Hwang et al, 2016;Goretti et al, 2017), wheat (Triticum aestivum; , and tomato (Solanum lycopersicum; Ben-Naim et al, 2006). Wenkel et al originally observed homology between the CCT domain and the conserved domain of NF-YA, suggesting that CO and NF-YA might both bind DNA with NF-YB/NF-YC HFD dimers (Wenkel et al, 2006).…”
Section: Nf-co and Nf-y In Floweringmentioning
confidence: 99%